2014
DOI: 10.3174/ajnr.a4179
|View full text |Cite
|
Sign up to set email alerts
|

Artery Length Sensitivity in Patient-Specific Cerebral Aneurysm Simulations

Abstract: BACKGROUND AND PURPOSE:The reconstruction of aneurysm geometry is a main factor affecting the accuracy of hemodynamics simulations in patient-specific aneurysms. We analyzed the effects of the inlet artery length on intra-aneurysmal flow estimations by using 10 ophthalmic aneurysm models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…The results of this study suggest that the location of the upstream boundary should not be placed just after the bifurcation. As for a bend, Hodis et al showed that a bend in the ICA renders a prominent difference in the results of the CFD, including velocities, WSS, and OSI inside a cerebral aneurysm (Hodis et al, 2015). However, in the present study, the relatively small difference between Models A and C implies that the assumption of a uniform velocity profile just after the bend has a small influence on the blood flow inside the aneurysm.…”
contrasting
confidence: 53%
“…The results of this study suggest that the location of the upstream boundary should not be placed just after the bifurcation. As for a bend, Hodis et al showed that a bend in the ICA renders a prominent difference in the results of the CFD, including velocities, WSS, and OSI inside a cerebral aneurysm (Hodis et al, 2015). However, in the present study, the relatively small difference between Models A and C implies that the assumption of a uniform velocity profile just after the bend has a small influence on the blood flow inside the aneurysm.…”
contrasting
confidence: 53%
“…The differences we report in hemodynamic indices due to outflow strategy, as shown in Fig 3, are comparable with those reported due to CFD solution strategy, 2 which were, in turn, far greater than those due to non-Newtonian viscosity. 21 Similarly, the divergent conclusions of Ramalho et al 16 and Venugopal et al 17 were drawn from TAWSS patterns that appear, qualitatively at least, to be comparable with those presented in studies of geometric [22][23][24] or inflow 3 uncertainties. Together these suggest that the outflow strategy should be considered at least as important as other assumptions or uncertainties in aneurysm CFD.…”
Section: Relationship To Previous Studies: Impact Of Outflow or Not?mentioning
confidence: 87%
“…Original stereolithography geometries were obtained from AneuriskWeb repository and edited for smoothness and branch elongations in Autodesk Meshmixer. Only models with long enough (at least 10 times the arterial diameter) original inlet branches were included in the current study to minimize the effect of nonphysiological boundary conditions . Some outlets were artificially extended downstream from the aneurysm dome or bifurcations to prevent boundary effects.…”
Section: Methodsmentioning
confidence: 99%
“…Only models with long enough (at least 10 times the arterial diameter) original inlet branches were included in the current study to minimize the effect of nonphysiological boundary conditions. 25,26 Some outlets were artificially extended downstream from the aneurysm dome or bifurcations to prevent boundary effects. For the purpose of capturing flow patterns independent of mesh element size, we generated uniform hexahedral dominant meshes with the element size of 0.08 mm, which was the smallest mesh resolution used in a comprehensive grid convergence study of Hodis et al 27 Computational meshes were generated using SnappyHexMesh from OpenFOAM.…”
Section: Patient-specific Simulations 221 Preprocessingmentioning
confidence: 99%